Kaidah Al-Adatu Muhakkamah dalam Perkawinan Adat : Khususnya Perkawinan Adat Dayak Ngaju dan Adat Banjar - Nor Harika; Ilham Perdana A; Khairunnisa Khairunnisa (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This research examines the implementation of the Islamic legal maxim "Al-'Ādatu Muḥakkamah" (custom can be established as law) in the context of Indonesian traditional marriages. Using a normative-empirical approach, the article analyzes the foundations of this maxim from the Qur'an and Hadith, as well as its application to the traditional marriage practices of the Dayak Ngaju and Banjar communities. The findings indicate that the Palaku tradition among the Dayak Ngaju community and the Jujuran tradition among the Banjar community demonstrate compatibility with Islamic legal principles through the application of the Al-'Ādatu Muḥakkamah maxim, although certain aspects require adjustment. This article also elaborates on efforts to harmonize Islamic law and customary law within Indonesia's national legal system. The research concludes that the Al-'Ādatu Muḥakkamah maxim provides a theoretical foundation that enables the accommodation of local cultural values within the framework of Islamic law, thus creating a legal system relevant to the socio-cultural context of Indonesian society.